SAT0306 SEMIQUANTITATIVE AND QUANTITATIVE ANALYSIS OF LUNG CT IN THE ASSESSMENT OF INTERSTITIAL LUNG DISEASE IN IDIOPATHIC INFLAMMATORY MYOPATHIES WITH A FOCUS ON ANTISYNTHETASE. (13th June 2020) - Barsotti, S.; Roncella, C.; Valentini, A.; Cavagna, L.; Castellana, R.; Cioffi, E.; Tripoli, A.; Caramella, D.; Bartholmai, B.; Neri, R.; Falaschi, F.; Romei, C.; et al.
Abstract : Background: Interstitial lung disease (ILD), is common in patients with idiopathic inflammatory myopathies (IIM) and strongly impact on patients' morbidity and mortality. Patients with anti-aminoacyl-transfer RNA-synthetases (anti-ARS) antibodies are associated with an increased risk of ILD. Objectives: Defining the radiological characteristics of IIM patients, with special focus on serological groups, through qualitative, semiquantitative and quantitative analysis of lung CT. Methods: This was a prospective study conducted from 2016 to 2019. Ninety-eight IIM patients (35 men, 63 women) were included. Myositis specific autoantibodies (MSA) were assessed with Myositis Prophyle III (Euroimmune, Lubeck). Each patient had a baseline CT; the total score of Warrick (WS) was obtained at semiquantitative analysis. The radiological scores ILD% (interstitial lung disease %) and PVRS% (pulmonary vascular related structure) were the result of quantitative analysis in 61 patients (CALIPER). Pulmonary function tests (PFTs) included TLC%, FVC% and DLCO% (65 patients). The analysis was conducted in the whole group and divided in subgroups based on their MSA pattern: in particular anti-ARS (Group 1) and patients negative to MSA (Group 2) were analysed. Results: Positive correlations between ILD% and PVRS% (Rho=0.916; ρ=0.000), WS and ILD% (Rho=0.663; ρ=0.000) and WS and PVRS% (Rho=0.637; ρ<0.001) were found. The most relevant inverse correlations were found between ILD% and DLCO% (Rho=-0.590; ρ=0.001), PVRS% and DLCO% (Rho=-0.549; ρ<0.001) and WS and DLCO% (Rho=-0.471; ρ<0.001). Statistically significant higher values of WS, ILD% and PVRS% were found in Group 1 (WS=15, ILD%=11 and PVRS%=3.5), compared to Group 2 (WS=2.5, ILD%=0.84 and PVRS%=2.2). NSIP pattern resulted dominant represented in the two groups (80% Group 1, 75% Group 2). No statistically significant differences of DLCO%, FVC% and TLCO% were found. Conclusion: The inverse correlations between the radiological scores and the functional data TLC% and DLCO% (ρ<0.001) confirm the role of lung CT in the clinical management of ILD in IIM patients, and may represent a promising tool for clinical trials. For the first time anti-ARS and serological negative patients were defined through qualitative, semiquantitative and quantitative analysis of lung CT. Further study should be conducted in order to define the prognostic value of the quantitative analysis of lung CT in the follow up of IIM patients. Disclosure of Interests: None declared